Very Rare Liver Neoplasm: Lymphoepithelioma-Like (LEL) Hepatocellular Carcinoma - Marcello Filotico; Valentina Moretti; Federica Floccari; Alessandro D’Amuri (Case Reports in Pathology)
A case of lymphoepithelioma-like (LEL) hepatobiliary carcinoma is reported. To date, only 89 cases of this rare neoplasm have been reported, with both hepatocellular and cholangiocellular histotype. The case reported here could be classified as LEL mixed hepatobiliary carcinoma (Hepato-Cholangio), a histotype not reported so far in the LEL variant.